Information Letter “On the Issue of Legal Wrongfulness in Establishing Witness Credibility through Forensic Evaluation” - S. A. Smirnova; E. V. Makushkin; A. Ya. Asnis; E. V. Vaske; E. G. Dozortseva; F. S. Safuanov; S. N. Shishkov; S. S. Shipshin; D. S. Oshevskii; D. V. Berdnikov; T. N. Sekerazh; A. N. Kalinina (Теория и практика судебной экспертизы)
This information letter was produced in response to a growing number of inquiries from investigators, and increased instances of forensic psychologists being appointed to evaluate witness credibility based on videos of interrogations. The letter addresses the need to streamline forensic casework related to the analysis of video recordings of specific investigative actions involving different agents of the criminal process. The letter considers possibilities for commissioning these forensic procedures and the rationale for conducting such examinations, in compliance with the scientific principles of professional forensic work.